Front Cover. Issue 2 (February 2017) - Gallien, Laure; Altermatt, Florian; Wiemers, Martin; Schweiger, Oliver; Zimmermann, Niklaus E.
Abstract : The cover image, by LAURE GALLIEN et al., is based on the Biodiversity Research Invasive plants threaten the least mobile butterflies in Switzerland, DOI:10.1111/ddi.12513 .